(untitled) (Journal of Hama University, 2026)
The study was conducted on 12 Holstien Friesen Cows in Syria to identifying the impact of plant- livgrow feed as Powder form on the activation of liver. The study confirmed that there was mark-able significant differences between control and trail groups, the last group was added the livgrow-feed Powder to Food the complete trail. From one day age to 60 days with concentrations (1 g /kg Food). The Activity of liver enzyme (AST-ALP-GLDH) in blood sera in day (0, 30, and 60 days) from the complete trail was less than 0.05 in all the breeding stages (p value > 0.05).